IMPLEMENTASI TATA KELOLA ORGANISASI DAN MANAJEMEN RISIKO REPUTASI PADA ORGANISASI NIRLABA (STUDI KASUS GEREJA BNKP JEMAAT KOTA PADANG - Halawa, Somah Taufik (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The church as a non-profit organization must be able to maintain its reputation to ensure the support of the parties in the sustainability of the organization by applying the principles of good corporate governance. To maintain its reputation, the church must be able to manage its reputation risk using a reputation risk management approach. Stakeholder theory approach to identify stakeholders and their expectations of organizational management. This study aims to observe the BNKP Jemaat Kota Padang Church in implementing the principles of good corporate governance and reputation risk management. The method used is descriptive qualitative method. The results of the study show that the BNKP Jemaat Kota Padang Church applies the principles of organizational governance through the rules of Church Administration and its risk management controls are carried out with various policies but do not have a well-developed risk management system or have a risk register.